Mechanisms of retention of PEGylated recombinant human deoxyribonuclease i (rhDNase) in the lungs - Mahri, Sohaib (2021)
Conjugation of recombinant human deoxyribonuclease I (rhDNase) to large (≥ 20 kDa) polyethylene glycol (PEG) has been shown to prolong the lung residence time of the enzyme in mice. Here, we investigated the mechanisms of this extended retention of PEG-rhDNase conjugates.